Love Your Self, Love People, Together We Are Stronger: Health Literacy For Better Health Behaviours - Harahap, Sarah Geltri; Sibualamu, Khalida Ziah; Hermawan, Catherine; Mailintina, Yurrita; Ellynia, Ellynia (Jurnal Pengabdian Kesehatan, 2025)
Digital literacy also plays a role in promoting proactive health behaviors. With good digital literacy, people can use health applications to monitor their health conditions, find information about disease prevention, and access health services online. The high number of infectious and non-communicable diseases is an important concern in the Society 5.0 era. This Community Service Activity (PKm) aims to increase the knowledge of adolescents about the importance of digital literacy for the sake of rehab at SMAN -2 Jakarta. The activity was carried out for two days involving 32 students of grade XII Science, using interactive learning media. Data collection was carried out in two cases, before and after counseling was given to evaluate student knowledge. The results of the evaluation showed that there was an improvement in the knowledge aspect of students with an n gain value of 52%. The t-dependent results showed a p value of 0.004 which means that there was a difference in adolescent knowledge before being given education and after being given education about health literacy. This finding confirms that PKm activities in the form of health education can increase students' knowledge at N-2 High School related to digital literacy about health.